Silencing NKD2 by Promoter Region Hypermethylation Promotes Esophageal Cancer Progression by Activating Wnt Signaling. Issue 11 (November 2016) - Cao, Baoping; Yang, Weili; Jin, Yongshuai; Zhang, Meiying; He, Tao; Zhan, Qimin; Herman, James G.; Zhong, Guanglin; Guo, Mingzhou
ABSTRACT : Introduction : Naked cuticle homolog 2 ( NKD2 ) was found to be frequently methylated in human breast and gastric cancers. However, the epigenetic changes and mechanisms of NKD2 in human esophageal cancer remain unclear. Methods : Nine esophageal cancer cell lines and 154 cases of primary esophageal cancer samples were analyzed using methylation‐specific polymerase chain reaction, immunohistochemical analysis, Western blot, and xenograft mouse models. Results : Loss of NKD2 expression and complete methylation were found in KYSE150 and TE1 cells. Reduced NKD2 expression and partial methylation of the promoter region were observed in KYSE30, KYSE70, KYSE410, KYSE140, and COLO680 cells. High levels of NKD2 expression and unmethylation were detected in KYSE450 and TE8 cells. Reexpression of NKD2 was induced by 5‐aza‐2′‐deoxycytidine in cells in which NKD2 was not expressed or cells in which NKD2 expression was reduced. NKD2 was methylated in 53.2% of human primary esophageal cancer samples (82 of 154), and promoter region hypermethylation was significantly associated with reduced expression of NKD2 ( p < 0.01). NKD2 methylation was associated with tumor, node, and metastasis stage and lymph node metastasis ( p < 0.01). Our results suggest that NKD2 is regulated by promoter region methylation and that methylation of NKD2 may serve as a prognostic marker in esophageal cancer. Our further studies demonstrate that NKD2 suppresses cell proliferation, colony formation, cell invasion, and migration and also induces G1/S checkpoint arrest in esophageal cancer cells. NKD2 suppressed xenograft tumor growth and inhibited Wnt signaling in human esophageal cancer cells. Conclusions : NKD2 is frequently methylated in human esophageal cancer, and the expression of NKD2 is regulated by promoter region methylation. NKD2 suppresses esophageal cancer progression by inhibiting Wnt signaling both in vitro and in vivo.